Magnetic-field-induced second harmonic generation in semiconductors and insulators - Sänger, Ingo (Technische Universität Dortmund, 2006)
In the first part, it is shown that application of a magnetic field induces optical second harmonic generation (SHG) in GaAs. This phenomenon arises from field-induced symmetry breaking causing new optical nonlinearities. A series of narrow SHG lines is observed in the spectral range from 1.52 to 1.77 eV that is attributed to Landau-level quantization of the band energy spectrum. The rotational anisotropy of the SHG signal distinctly differs from that of the electric-dipole approximation. Model calculations reveal that nonlinear magneto-optical spatial-dispersion that comes together with the electric-dipole term is the dominant mechanism for this nonlinearity. In the second part, basically different mechanisms of optical second harmonic generation (SHG) in semiconductors, induced by an external magnetic field H, are identified experimentally by studying the diluted magnetic semiconductor (Cd,Mn)Te. For paramagnetic (Cd,Mn)Te the SHG response is governed by spin quantization of electronic states, in contrast with diamagnetic CdTe with its dominating orbital quantization. The mechanisms can be identified by the distinct magnetic field dependence of the SHG intensity which scales with the spin splitting in the paramagnetic case as compared to the H2 dependence observed for the diamagnetic case. In the third part, three types of optical magnetic-field induced second harmonic (MFISH) generation are discussed in CuB2O4. Unusually sharp and intense electronic transitions in MFISH and linear absorption spectra provide selective access to the two nonequivalent Cu2+ sublattices. The magnetic phase diagram for both sublattices is determined by MFISH. Magnetic structure is dominated by antiferromagnetic order at the 4b site. Sublattice interactions transfer it to the 8d site where it coexists with a discoupled paramagnetic component.
Magnetic field induced second harmonic generation in semiconductors and insulators
Keywords: SHG; Semiconductor; Insulator; Magnetism; Magnetic; Optic; DMS; GaAs; CdTe; Nonlinear; Spectroscopy; NiO; 530